Comparative assessment of the diagnostic efficiency of medical imaging methods, as exemplified by magnetic resonance imaging and contrast-enhanced ultrasound examination, based on propensity score matching - E. A. Busko; A. B. Goncharova; D. A. Buchina; A. S. Natopkina (ABV-press, 2021)
Objective: сomparative assessment of the diagnostic efficiency of magnetic resonance imaging (MRI) and contrastenhanced ultrasound examination in the primary diagnosis of breast cancer based on propensity score matching.Materials and methods. From 2017 to 2018 on the basis of the National Medical Research Center of Oncology named after N.N. Petrov 176 women with various complaints of breast diseases were examined using MRI, which was carried out on a Magnetom Aera (Siemens) and Signa Excite HD (GE) apparatus with a magnetic field strength of 1.5 T and special surface breast coil. From 2018 to 2019 on the basis of the National Medical Research Center of Oncology named after N.N. Petrov 277 women with various complaints of breast diseases were examined using multiparametric ultrasonography (US) consisting of gray-scale US, color Doppler US, strain US, and contrast enhanced US, performed on a Hitachi Hi Vision Ascendus ultrasound scanner using a linear transducer in the frequency range 5-13 MHz. To verify the lesions, the patients underwent histological or cytological examination. The results of ultrasound examination, histological and cytological conclusions were entered into the database containing 453 diagnostic records: 277 were obtained using the multiparametric US and 176 - using the MRI method. To solve the problem, the propensity score matching algorithm was used: building a model, calculating conditional probabilities, balancing, checking the balance quality, evaluating efficiency. The main and auxiliary characteristics of the methods of MRI and contrast-enhanced ultrasound before and after the selection of pairs are given in the work.Conclusion. The proposed algorithm is implemented in the R language. The results of the program are that both diagnostic methods showed excellent results, 95 % confidence intervals almost completely overlap, from which a preliminary conclusion should be made that these methods are equivalent in efficiency in the primary diagnosis of breast cancer.